Creating Innovation of Public Value Through Management Information Systems - Rofi, Aliyyu; Putra, Fadillah; Sentanu, I Gede (Research and Development Agency Ministry of Home Affairs, 2021)
The use of information technology cannot be escaped from everyday life in society. In the context of improving the public sector, the government is required to improve performance, responsibility, and public trust and focus more on providing better services by revitalizing public administration by increasing transparency and prioritizing service quality. The Bureau of Personnel uses the â€œSIMPEGâ€ application in the form of digitizing the public sector which is considered an extraordinary opportunity to create public value. This research is focused on the approach of the SIMPEG pre and post-mobile SSO. The method adopted by this study was mixed methods. The implementation of SIMPEG mobile SSO at the Ministry of Home Affairs has fulfilled the three aspects of the public values â€‹â€‹stated by Moore, namely legitimacy and support, operational capabilities, and public value. However, based on the findings within the field, some things are still not appropriate. For example, there is still the use of paper-based administration, so that the mobile SSO service has not been optimized. Based on the dimensions of system quality, information quality, and service quality, SIMPEG based on web-based are categorized as quite sustainable, whereas after using SIMPEG mobile SSO application was classified as very sustainable. When viewed from the results of stress and RSQ values, it can be said that the results of the MDS in this study describe a good model and can represent the problems being discussed and conclude that only SIMPEG mobile SSO application is recommended for sustainability.